Development of an electric vehicle charging management system using global navigation satellite system - Lim, Derrick Jun Hua (2015)
With the increased in environmental awareness over the recent years, many countries have been seeking for cleaner method to generate electricity in order to reduce pollution in the environment. One of the products that contribute to polluting the environment is internal combustion engine (ICE) vehicles. Generally, ICE is normally powered by combustion of petroleum products such as diesel fuel or gasoline. Even though climate change is a natural process, the increase in the concentrations of greenhouse gases produced in the combustion process will contribute to a further increase of the earth’s temperature. At such, Electric Vehicles (EVs) which are more efficient as compared to ICE are considered as a more sustainable mode of transport in Singapore. Furthermore, they are more environment friendly as there are no carbon emission as well as more cost-saving. However, the limited number of charging stations in Singapore is a major concern that deters the drivers from changing into EVs, as the difficulty of locating a charging station might cause inconvenience to the drivers. Hence, this project looks into developing a charging management system (CMS) using the android platform for the convenience of the drivers. This system uses the Global Positioning System (GPS) which uses a GPS receiver to determine the location of the EVs, charging stations and then calculates the distance and time taken for the EVs to reach the nearest charging station. It also calculates the battery state-of-charges (SoCs) with a Bluetooth Module to decide whether there is enough power for the EV to reach the charging stations and then guides the user to the destination whenever a charge is required. This CMS aims to remove the fear of running out of power and the inconvenience of locating the charging stations so as to promote more drivers to switch to EV.